Risk-based winterization to prevent hydrate formation in northern harsh environment - Herath, D; Faisal Khan; Yang, M (2016)
With the increasing demand for energy around the globe, hydrocarbon explorations move towards the Arctic region that holds a majority of unexploited oil reserves. The harsh environmental conditions with sub-zero ambient temperatures and high winds demand winterization techniques for pipes, instruments and equipment to carry out uninterrupted plant operations. The natural phenomenon: hydrate formation, is considered to be a major flow assurance problem starting from the wellhead through the final point in the delivery system which could be addressed through winterization. Developing winterization strategies for arctic conditions is a challenging task demanding rigorous and robust approaches. Risk-based winterization is a novel approach, adapted for vessels operating in arctic environments. In this paper a new model is proposed to calculate the probability of hydrate formation and its associated risk for a given loading scenario. The winterization requirement is determined based on the estimated risk. Two case studies presented here demonstrate the applicability of the proposed model and compare several winterization methods to find an optimal solution.